Penentuan nilai field capacity pada sampah segar Dan sampah lama - Samin . (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
In determining leachate generation, the value of field capacity waste is one of the parameters that determine the amount of leachate which is formed against, because the field capacity (FC) is amount of water that may be stored by the waste until it has saturated the water and ultimately if the water entering the landfill waste then the water will come out into leachate. In this study we have performed research on the determination of field capacity on fresh waste and old waste. The results of this research showed that the value of FC is influenced by age waste. The value of field capacity (FC) on fresh waste is greater than old waste and the value of field capacity (FC) influenced by material density. The value of field capacity (FC) materials with higher density (black sand), the value of field capacity (FC) is smaller.Keywords: leachate, field capacity, waste